2016
DOI: 10.1111/jgs.14528
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Potentially Inappropriate Prescribing of Proton Pump Inhibitors in Older People in Primary Care in Ireland from 1997 to 2012

Abstract: 275Word count: 2614

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…Proton pump inhibitors (PPIs) are widely used in this population, with a weighted prevalence estimate of 18.5% of community‐dwelling older adults using them in a 2010–11 cohort . The 2015 Beers Criteria recommend against the use of PPIs for longer than 8 weeks except in high‐risk individuals, but many clinicians may not be following this recommendation . This warning was based on the risks of Clostridium difficile infection (CDI) and bone loss and fractures.…”
Section: Important Side Effects Of Drugs Commonly Prescribed In Primamentioning
confidence: 99%
“…Proton pump inhibitors (PPIs) are widely used in this population, with a weighted prevalence estimate of 18.5% of community‐dwelling older adults using them in a 2010–11 cohort . The 2015 Beers Criteria recommend against the use of PPIs for longer than 8 weeks except in high‐risk individuals, but many clinicians may not be following this recommendation . This warning was based on the risks of Clostridium difficile infection (CDI) and bone loss and fractures.…”
Section: Important Side Effects Of Drugs Commonly Prescribed In Primamentioning
confidence: 99%
“…Various studies have shown that patients entering and leaving the hospital with continuous PPI prescriptions often do not have these medications reconciled and frequently receive log‐term treatment without proper indication . Long‐term PPI use is defined by various studies as 8 or more weeks of daily drug utilization . As the concerns related to adverse effects due to long‐term drug usage and the concern for inappropriate long‐term PPI therapy continue to increase, practice patterns in the discussed specialties seem to thus far be unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…drugs worldwide [1][2][3][4]. A number of studies have suggested, however, that many patients are prescribed PPIs inappropriately [5][6][7][8].…”
mentioning
confidence: 99%